The Influence of Financial Ratios and Investment Decisions On Stock Prices - Aradhana, Danu; Sofyaun, Ashari; Matyani, Matyani (Riwayat: Educational Journal of History and Humanities, 2025)
Financial and market ratios describe a relationship based on considerations between a certain amount and another amount. This ratio explains the good or bad condition of a company's financial position, especially when the figure is compared to the comparative figure used as a standard. The financial ratios in this study include leverage and profitability, while the market ratio is related to investment decisions. The documentation method is used in collecting research data with secondary data types in the form of annual reports of pharmaceutical sub-sector companies on the Indonesia Stock Exchange for the period 2019-2023. The findings show that partially Debt to Equity and Return on Equity do not affect stock prices. Price Earning Ratio has a positive effect on stock prices.